Al-Jaḥiẓ's Techniques in His Book "Kitab Al- Bayan Wa Al-Tabyin" (“Elegance of Expression and Clarity of Exposition”) – A Critical Study - Lateef, Hasan Saad (International Journal of Psychosocial Rehabilitation, 2020)
This research basically focuses on one of the distinctive techniques of writing used by Al-Jahez as one of the most outstanding writers of Arabic literature during the Abbasid era; exclusively in his famous book: Kitab Al-Bayan wa Al-Tabyin. In this book, there is a variety of technical styles, which Al-Jahez used in his writings about general or private subjects. He invested those styles in so creative texts of Arabic literature, which made Kitab Al-Bayan wa Al-Tabyin as one of the most distinguished books of Arabic literature. Therefore, the book still attracted more readers and scholars due to the richness of its rhetorical arts. So this study concentrated on revealing the details of these different styles, which made Al-Jahez as a more distinctive writer than his contemporaries and his distinguished way of writing as a subject for literary criticism